Self-medication practice for dental pain: expectations and rationality / Zaty Ainaa Mohamed ... [et al.] - Mohamed, Zaty Ainaa; Azman, Nur Farhaanah; Masud, Mahyunah; Abdul Rahim, Mohd Aizat; Abu Hassan, Mohamed Ibrahim (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Self-medication (SM) is the use of medicines by people who take drugs without the advice of doctors. Purpose: To determine the prevalence of SM for dental pain, to compare the contributing factors, perception, and awareness regarding the practice among medical, dental and, pharmacy students. Methods: This observational study was conducted among 573 year1 and year5 students undergoing the teaching of pharmacology. The validated questionnaires were distributed during the beginning of the years. Data were analyzed using SPSS version 23. Results: The experience of dental pain by the students was 69-87%. The prevalence of SM among year1 and year5 were 30% and 49% (medical), 37% and 61% (dental), 46% and 57% (pharmacy) respectively with pharmacy year1 scoring highest at 46% and dental year5 at 61%. Both years medicated with analgesic at 17-33% while 35-70% opted for saltwater, ice packs, and others. The medical and pharmacy students perceived that they do not have a good ability to diagnose symptoms of dental pain. The majority was aware of drug interactions and expiratory dates. Conclusion: As expected, the year5 self-medicated more than the year1, made easy by the gain in knowledge and accessibility to medicines. Their perception and awareness rationalize them as future prescribers for medication.